The Trade Assortment: The Meanings of Merchandise in the Ojibwa Fur Trade - White, Bruce M. (Vingt ans après, Habitants et marchands: lectures de l'histoire des XVIIe et XVIIIe siècles canadiens, 1998)
Keywords: Autochtones; Fourrure; Marchands

Les Indiens, la fourrure et les Blancs - Trigger, Bruce Graham (Boréal et Seuil, 1992)
Translators: _:n15850
Keywords: Autochtones; Fourrure; Français

Ne faire qu'un seul peuple? Iroquois et Français à l'"âge héroïque" de la Nouvelle-France (1600-1660) - Beaulieu, Alain (Université Laval, 1992)
Keywords: Autochtones; Français; Iroquois

Natives and Newcomers: Canada's "Heroic Age" reconsidered - Trigger, Bruce Graham (McGill-Queen's University Press, 1994)
Plusieurs réimpressions
Keywords: Autochtones; Français; Iroquoiens; Iroquois